Advanced bioreactor system for the implantable biomaterials testing and tissue engineering applications - Ramdan, M. (Asian Research Publishing Network, 2017)
Tissue engineering scientists believe that the next generation of functional tissue and artificial organ replacements truly need the use of advanced bioreactor system. Bioreactor system, in which the culture conditions can be adjusted and studied, will support the development of tissues with optimal mechanical, chemical, and biological stimuli for a given application. Although there have been various types of bioreactors designed and tested for several implantable biomaterials and tissue engineering applications, the development of a complete artificial organ remains a dream. This review addresses recent advances and future challenges in designing and using advanced bioreactor system to support the mass production of vascularized engineering tissues and artificial organ. The potential application of micro-electromechanical system (MEMS) bioreactor technology for future advancement in tissue engineering is also highlighted.